Market Behavior of Continental Ornamental Fish in Colombia - Franco Ortega, Julio Alejandro; Moncaleano Gómez, Erika Marcela; Ajiaco Martinez, Rosa Elena (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper addresses a review of scientific literature on the commercial importance of ornamental fish (PO) in Colombia. As the main results, it was found that this market is still a global exchange activity for exotic species that generates great profits and that it has been sustained with the trade of more than one billion species each year. Most of the POs are extracted from natural populations and end up in aquariums worldwide distributed, generating depletion of the resource associated with overfishing and extraction activities. Capture and handling practices and high mortality rates represent a significant welfare problem as well as a significant economic and environmental cost for the industry. South America is still the largest species supplier, mainly the biodiverse countries with an export tradition such as Colombia, where it is constituted as a commercial or subsistence resource of great importance for the fishing and indigenous populations. A list of 522 species of PO confirmed, grouped in 13 Orders, 49 Families and 213 genera whose most desirable species are Osteoglossum bicirrhosum, Osteoglossum ferreirai, Paracheirodon axelrodi, Pterophyllum altum, Panaque nigrolineatus and Callichthyidae Callichthyidae. The problems associated with the few studies carried out in PO, the limited legislation that regulates and protects ecosystems and their biodiversity, added to bad practices and incentives for cultivation, abandonment of fishing communities that depend on this resource, have limited the growth of the sector. It is urgent to consider sustainable alternatives for reducing fishing pressure on the species, which include health, nutritional and efficient use of the water resource in order to allow the use and conservation of PO species, in this way this trade would grow much more trade and its contribution to the country's economy would also be grater.